ANXA2 enhances the progression of hepatocellular carcinoma via remodeling the cell motility associated structures. (June 2016) - Shi, Hongyan; Xiao, Li; Duan, Wei; He, Huimin; Ma, Lele; Da, Miaomiao; Duan, Yan; Wang, Qian; Wu, Huayi; Song, Xigui; Hou, Yingchun
Highlights: ANXA2 enhances HCC growth by up-regulating cell proliferation without significant apoptosis enhancement. ANXA2 enhances the HCC cell motility by up-regulating expression and polymerization of cell microstructure associated proteins, F-actin, β-tubulin and lamin B. ANXA2 enhances HCC metastasis by introducing development of the cell psuedopodia/filapodia closely associated with cell motility and contact inhibition. Take above together, ANXA2 enhances malignancy of HCC cells by remodeling motility associated microstructures. Abstract: Hepatocellular carcinoma (HCC) ranks as the fifth most common malignancy worldwide. The detailed mechanism of signal regulation for HCC progression is still not known, and the high motility of cancer cells is known as a core property for cancer progression maintenance. Annexin A2 (ANXA2), a calcium-dependent phospholipids binding protein is highly expressed in HCC. To study the roles the excessively expressed ANXA2 during the progression of HCC, we inhibited the ANXA2 expression in SMMC-7721 cells using RNAi, followed by the analysis of cell growth, apoptosis and cell motility. To explore the relationship between the cell behaviors and its structures, the microstructure changes were observed under fluorescence microscopy, laser scanning confocal microscopy and electron microscopy. Our findings demonstrated that down-regulation of ANXA2 results in decreased the cell proliferation and motility, enhanced apoptosis, suppressed cell pseudopodia/filopodia, inhibited expression of F-actin and β-tubulin, and inhibited or depolymerized Lamin B. The cell contact inhibition was also analyzed in the paper. Take together, our results indicate that ANXA2 plays an important role to enhance the malignant behaviors of HCC cells, and the enhancement is closely based on its remodeling to cell structures.